Women with Hijab in the Advertisement: Between Identity Politics, Religious Commodification and the Deconstruction on the Meaning of Beauty - AD. Kusumaningtyas; Imam Tabroni; Muhammad Ridwan Effendi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
There are so many attractiveness of advertising messages on why an advertisement is made. Generally, an advertisement was made to persuade the public or consumers candidates for buying and consuming a certain product. If previously, several advertisements for products mostly use the beautiful women with certain indicators such as white skin, long black hair, thin and sexy body; recently seems to show a trend by using the veiled woman (woman who wears hijab) as its models. There must be many interpretations regarding this symbol. For example about the dakwah messages on Muslim women's identity that are performed through their way of dressing up, religious commodification because the appearance of a Muslim woman will attract the attention of Muslim consumers, the deconstruction of the meaning of beauty, or a combination of several attractions of the advertising message that was represented by woman with the hijab. This article will analyze about those various symbol interpretations.